Sequential cleavage and blastocyst embryo transfer and IVF outcomes: a systematic review - Jianeng Zhang; Chong Wang; Huanhuan Zhang; Yan Zhou (BMC, 2021)
Abstract Background Sequential embryo transfer has been proposed as a way to improve embryo implantation in women for in vitro fertilization (IVF), but the effect on pregnancy outcomes remains ambiguous. This systematic review was conducted to investigate the efficacy of sequential embryo transfer on IVF outcomes. Methods A literature search was performed in the PubMed, Web of Science, Cochrane Library, ScienceDirect and Wanfang databases. Data were pooled using a random- or fixed-effects model according to study heterogeneity. The results are expressed as relative risks (RRs) with 95% confidence intervals (CIs). Heterogeneity was evaluated by the I2 statistic. The study protocol was registered prospectively on INPLASY, ID: INPLASY202180019. Results Ten eligible studies with 2658 participants compared sequential embryo transfer and cleavage transfer, while four studies with 513 participants compared sequential embryo transfer and blastocyst transfer. The synthesis results showed that the clinical pregnancy rate was higher in the sequential embryo transfer group than in the cleavage embryo transfer group (RR 1.42, 95% CI 1.26-1.60, P< 0.01) for both women who did experience repeated implantation failure (RIF) (RR 1.58, 95% CI 1.17-2.13, P< 0.01) and did not experience RIF (Non-RIF) (RR 1.44, 95% CI 1.20-1.66, P< 0.01). However, sequential embryo transfer showed no significant benefit over blastocyst embryo transfer. Conclusion The current systematic review demonstrates that sequential cleavage and blastocyst embryo transfer improve the clinical pregnancy rate over conventional cleavage embryo transfer. For women with adequate embryos, sequential transfer could be attempted following careful consideration. More high-grade evidence from prospective randomized studies is warranted.